Rivalry Versus Hate: Measuring the Influence of Promotional Titles and Logos on Fan Rival Perceptions - Cody T. Havard; Daniel L. Wann; Frederick G. Grieve (Journal of Applied Sports Management, 2018)
The current study used an experimental design to examine how exposure to promotional titles and logos can influence fan rival perceptions. Students attending two schools that moved athletic conferences, and therefore, began rivalries with teams in their new conference, were exposed to either a neutral or negative fabricated title and logo meant to promote the new rivalry. They then reported their perceptions of the rival team. Results showed that students exposed to the neutral title were less likely to support their rival against another team than students exposed to the negative title. Further, students exposed to the negative title believed their rival fans behaved more poorly. Important implications and ways practitioners can use the data are discussed. Subscribe to JASM
Keywords: Rivalry; Fan Rival Perceptions; Promotional Titles and Logos; Promotion of Rivalry; Experimental Design